Evaluating the Impact of Marketing, Organisational and Process Innovation on Innovation Output of Information Technology Firms: Czech Republic and Estonia - ANDERSON, HENRY JUNIOR; STEJSKAL, JAN (Vysoká škola ekonomická v Praze, 2019)
Abstract Purpose: As technological innovation has enabled Information technology (IT) to seamlessly merge into daily routines playing an irreplaceable role in innovation generation and dissemination the research aims to assess the impact of marketing, organisational and process innovation on innovation in Czech Republic and Estonia. Design/methodology/approach: Data from Community Innovation Survey (2012-2014) was used whilst multiple regression analysis. 395 firms were selected for both Czech Republic and Estonia. These member states were selected due to their dwindling performance on the innovation scale relative to EU in 2010; IT and information service firms was also chosen as the unit of analysis. Findings: Public funding at the National and European Union level was only significant to innovation output in Estonia whilst organisational innovation was insignificant in both countries. Process innovation was significant to innovation output although with different direction of significance between both countries whilst marketing innovation variables were also fully significant in Czech Republic but partly significant in Estonia. Research/practical implications: The study provides insights into innovation behaviour of the Czech and Estonian companies. Originality/value: Furthering the innovation report of European Union and selectively focusing on the key innovation variables, the paper adds to the literature by detailing the response of the innovation output of Czech Republic and Estonia to marketing, organisational and process innovation of IT and information service firms.
Hodnocení dopadu marketingové, organizační a procesní inovace na inovační výstup firem v oblasti informačních technologií: Česká republika a Estonsko
Keywords: Keywords: Marketing Innovation, Organisational Innovation, Process Innovation, Czech Republic, Estonia; Klíčová slova: Marketingová inovace, Organizační inovace, Procesní inovace, česky Republika, Estonsko